Penyebab Penghambat Sertifikat Cara Pembuatan Obat Tradisional yang Baik dalam Implementasi Legalitas Obat Tradisional: Studi pada Industri Obat Tradisional di Kalimantan Selatan - Muhammad Rafif Ridwan; Yulia Qamariyanti (AHKAM, 2026)
This study was motivated by the need to understand inhibiting factors in obtaining the Good Traditional Medicine Manufacturing Practices (CPOTB) certificate as a legal prerequisite for traditional medicines in South Kalimantan, given that the CPOTB certificate is an official document confirming that traditional medicine industries have met quality and safety standards in accordance with the regulations of the Badan Pengawas Obat dan Makanan (BPOM). This study aimed to analyze the main barriers faced by business actors in the CPOTB certification process. The study employed an empirical legal approach with a case study of several traditional medicine industries in South Kalimantan classified under KBLI 21022. The findings showed that of 281 business actors, only 7 successfully obtained CPOTB certification. The main barriers identified included limited capital to meet the requirements for constructing permanent production facilities and procuring standard-compliant equipment, a shortage of competent human resources for quality management and documentation, and the complexity of administrative procedures and compliance with technically demanding requirements. These findings indicate that the current configuration of CPOTB regulations and technical requirements tends to burden micro and small enterprises, thereby constraining the expansion of legal compliance for traditional medicines. The study concludes that more adaptive and phased certification policies are needed so that micro and small enterprises can realistically meet CPOTB standards without excessive burden, while safeguarding the quality and safety of traditional medicine products.